2021
DOI: 10.1002/pei3.10060
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐stress tolerance: Mild nitrogen (N) deficiency effects on drought stress response of tomato (Solanum lycopersicum L.)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Drought and N deficiency induce adaptative responses such as root elongation, cell-damaging ROS production, and photosynthesis reduction. For example, reactive oxygen species (ROS) levels were reported to elevate in certain root areas during N deficiency due to reduced photosynthesis caused by drought stress (Safavi-Rizi et al, 2021). Previous studies have reported that drought stress affects the expression of key genes or QTLs associated with nitrogen management in rice.…”
Section: Introductionmentioning
confidence: 99%
“…Drought and N deficiency induce adaptative responses such as root elongation, cell-damaging ROS production, and photosynthesis reduction. For example, reactive oxygen species (ROS) levels were reported to elevate in certain root areas during N deficiency due to reduced photosynthesis caused by drought stress (Safavi-Rizi et al, 2021). Previous studies have reported that drought stress affects the expression of key genes or QTLs associated with nitrogen management in rice.…”
Section: Introductionmentioning
confidence: 99%